EFFICACY OF HUMIC STIMULANTS IN PRE-SOWING TREATMENT OF CEREAL SEEDS - Marenych, M. M.; Hanhur, V. V.; Popova, К. М.; Liashenko, V. V.; Kabak, Y. I. (Scientific Progress & Innovations, 2020)
Humic substances are important elements of field crops cultivation technology, the using of which can influence plant growth and development in fact during all stages of organogenesis. The purpose of the study was to determine the effectiveness of disinfectants and humic stimulants on the processes of seed germination, formation of spring barley and winter wheat productivity characteristics, and the prospects of their applying in production. The following scientific methods were used during the research: analysis, synthesis, field, and statistical. Statistically established nature of signs’ interrelations, which were studied in the experiment, showed that the main parameters of forming winter wheat productivity were grain weight per plant and productive tillering and of spring barley – thousand-kernel weight. However, yield capacity of grain crops is determined according to a more complex system, because productivity structural elements of crops, thousand-kernel weight, grain weight per plant, and the number of productive shoots, in particular, have direct correlation with yield (r=0.34–0.71), and they, in their turn, depend on plantlet root weight. It has been estimated that there is direct average degree correlation (r=0.54) between plantlet root weight and the number of productive stems, and strong correlation (r=0.85) between plantlet root weight and grain weight per plant. The results of mathematical analysis prove the importance of pre-sowing seed treatment for the formation of plant root system, which in future will be able to affect yield formation directly (r=0.44). According to the results of the research, it has been established that humate application positively influenced the growth of the above-ground part of spring barley. In case of winter wheat seed treatment, a considerable natural effect of this technology element on plant biometric parameters was registered, however, crop variety characteristics were also of considerable importance. Applying humic preparations for pre-sowing UB seed and 1R seed treatment resulted in plantlet weight increase by 8–19.6 %, and in wheat – within 11– 16 %. Potential yield increased by 8.8–12.7 and 28.3 %, respectively.